Coincidence Fixed-Point Theorems for p-Hybrid Contraction Mappings in Gb-Metric Space with Application. (8th December 2022) - Wangwe, Lucas
Abstract : By combining the notions of G -metric space and b -metric space, in this paper, we present coincidence fixed-point theorems for p -hybrid mappings in G b -metric spaces. An example is given to demonstrate the novelty of our main results. Henceforth, the illustrative applications are given by using nonlinear fractional differential equations.